Congenital tufted angioma. Case report. - El Fekih, N.; Litaim, N.; Jones, M.; Fazaa, B. (European Journal of Pediatric Dermatology, 2012)
Tufted angioma is a rare, benign cutaneous angiomatous proliferation, which often presents in the first few years of life. Lesions are most commonly reported to persist and/or expand over time. Congenital cases are rare, as are reports of spontaneous regression. Here is reported a histopathologically confirmed congenital tufted angioma. A wait and see policy should be considered for otherwise uncomplicated congenital or early infantile cases of tufted angioma.